Perbandingan Haversine Formula dan Euclidean Distance dalam Pencarian Jarak Terdekat Rumah Penampungan Hewan (Shelter) - Sarwati Rahayu; Fanni Ramziani; Bima Kuswara (Jurnal Ilmiah FIFO, 2022)
Animal cages (shelters) and animal hospitals still receive less attention from some people, and also lack of information and education about the number of animals (shelters) and animal hospitals, animal shelters have a noble mission for abandoned or abandoned animals by their owners. as well as hospitals where people can bring their pets for treatment while keeping their pets so that we as owners know what our animals are suffering from at that time and also to avoid diseases that can harm us as owners. Geographic Information System (GIS) has the ability to present information in graphic form using a map as an interface, so that it can be used as a presentation of information related to animal shelters. where the public can obtain data and information about animal shelters for personal and organizational or agency needs. The development researcher uses the haversine algorithm to be used as a search for the closest distance between the user and the location of the animal's house, as well as the Euclidian distance as a comparison to find the appropriate distance accuracy. From the results of these calculation it can be concluded that haversine and google maps this method has an accuracy level that is almost close to accurate with a percentage value of 99.88% with manual calculationsKeywords: website, haversine, euclidian, animal shelter